2011
DOI: 10.1111/j.1440-1843.2010.01901.x
|View full text |Cite
|
Sign up to set email alerts
|

Secretory leukocyte protease inhibitor inhibits neutrophil apoptosis

Abstract: Our findings indicate upregulation of SLPI in response to LPS in nasal secretions and show anti-apoptotic effects of SLPI in primary human neutrophils suggesting a new role of SLPI during neutrophilic inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 42 publications
0
17
0
1
Order By: Relevance
“…46,47 High levels of SLPI have been demonstrated in cancer cells, including ovarian cancer, gastric cancer, and oral squamous cell carcinoma, 46,48 and SLPI is involved in the proliferation 48-50 and survival of tumor cells and neutrophils. 30,31 Consistent with this, myeloid cells of SLPI-deficient CN patients exhibit cell-cycle arrest and elevated apoptosis. [11][12][13][14] Some of the activities of SLPI are independent of its protease inhibitory activity.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…46,47 High levels of SLPI have been demonstrated in cancer cells, including ovarian cancer, gastric cancer, and oral squamous cell carcinoma, 46,48 and SLPI is involved in the proliferation 48-50 and survival of tumor cells and neutrophils. 30,31 Consistent with this, myeloid cells of SLPI-deficient CN patients exhibit cell-cycle arrest and elevated apoptosis. [11][12][13][14] Some of the activities of SLPI are independent of its protease inhibitory activity.…”
mentioning
confidence: 58%
“…29 SLPI also exhibits antiapoptotic activity through binding to annexin II on the cell surface 30 and has been shown to protect granulocytes from apoptosis. 31 Intriguingly, SLPI is also known to modulate intracellular signal transduction pathways, such as nuclear factor kB (NF-kB) and extracellular signal-regulated kinase (ERK). [32][33][34] In this latter context, it has been shown that SLPI is involved in the activation (phosphorylation) of ERK1/2 protein, 33 which plays an important role in G-CSF-triggered myeloid differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, when we considered up-regulated genes in this enriched group separately, the innate immune response in particular was featured. For example, Secretory Leukocyte Peptidase Inhibitor (SLPI) and Azurocidin 1 (AZU1) are chemotactic for cells of the innate immune system and modulate the inflammatory response (Sallenave, 2002;Soehnlein et al, 2008;Subramaniyam et al, 2011). Lipocalin 2 (LCN2) is up-regulated during inflammation and in the plasma of patients with mild cognitive impairment (Choi et al, 2011), and is induced by IL-1b, a protein elevated in the CSF of first episode schizophrenia patients (Cowland et al, 2003;Soderlund et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The role of elastase in neutrophil apoptosis has been considered, and a recent study demonstrated that the secretory leukocyte protease inhibitor SLP1 could inhibit neutrophil apoptosis [37]. Upon PMA activation and ROS production, neutrophil-derived elastase translocates to the nucleus and aids in chromatin decondensation leading to NETosis [28].…”
Section: Discussionmentioning
confidence: 99%